2015
DOI: 10.1002/adem.201500143
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformations in Ti–Fe Alloys Induced by High‐Pressure Torsion

Abstract: The Ti-Fe alloys are quite important among various Ti-based alloys doped with b-stabilisers. Severe plastic deformation by the high pressure torsion (HPT) leads to the strong grain refinement in Ti-Fe alloys. The high-pressure vTi-phase appears during HPT of the Ti-1 wt.% Fe alloy. However, the vTi does not appear after uniaxial compression at the same pressure, without torsion. vTi remains quenched after pressure release and disappears by heating around 140-150°C. However, the further alloying with iron suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(37 citation statements)
references
References 33 publications
4
30
0
3
Order By: Relevance
“…The torsion torque increased during 1-2 anvil rotations in all alloys and pure Ti and then remained almost unchanged. In other words, it reached a steady state, as was observed previously in other alloys [16][17][18][19][20]51,52]). The central part (about 3 mm in diameter) of each disk after HPT was excluded from further investigations (since it is low-deformed).…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…The torsion torque increased during 1-2 anvil rotations in all alloys and pure Ti and then remained almost unchanged. In other words, it reached a steady state, as was observed previously in other alloys [16][17][18][19][20]51,52]). The central part (about 3 mm in diameter) of each disk after HPT was excluded from further investigations (since it is low-deformed).…”
Section: Methodssupporting
confidence: 83%
“…A number of SPD techniques include the application of high pressure, especially the high pressure torsion (HPT) one. It is known that the combination of shear strain with high pressure (i.e., in case of HPT) decreases the onset of the α → ω transition in comparison with quasi-hydrostatic conditions [2,[49][50][51]. The goal of this work is to study how the Co addition to Ti influences formation of the ω-phase under HPT.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several works investigated the phase transformations in the Ti–Fe system being induced by a high‐pressure torsion process (HPT) and the thermal stability of the pressure induced phases . The comparison of these findings with the results of the present work shows very interesting similarities in the transformation pathway upon heating, which will be discussed in the following.…”
Section: Resultssupporting
confidence: 67%
“…In these works, it was shown that the transformation of α′ and β to the high‐pressure ω phase strongly depends on the iron composition. The smallest lattice mismatch between the β and ω lattices was found for an Fe content of approx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation